The environment [Technology 2000 analysis and forecast]. - Perry, T.S (IEEE spectrum)
The author describes how research into making today's increasingly pervasive electronic products more environmentally safe is being spurred by concerns at both the global level-environmental contamination that will last for generations-and the personal level-the health of an individual